Preparation, characterization and performance evaluation of fly ash-based composite geopolymer membranes for methylene blue dye removal - Ahmad Daud, Nurul Amira; Shamsuddin, Muhammad Rashid; Ayu Pradanawati, Sylvia; Rabat, Nurul Ekmi (Science, Engineering and Health Studies, 2021)
Utilization of fly ash-based geopolymer membranes for the removal of environmentally hazardous materials has become an attractive route due to its cheaper processing cost and durability. This paper reported the preparation of geopolymer composite membranes and its performance for the removal of methylene blue contaminant. The geopolymer membrane was prepared by dissolving fly ash in alkaline activator of sodium hydroxide solution. Various proportions of foaming agents made from a mixture of hydrogen peroxide and egg white was added to investigate their influence on the membrane pore structures and morphology. The morphology, pore structure and functional groups of geopolymeric composite membranes were characterized using field emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET) analysis and Fourier transform infrared spectroscopy (FTIR), respectively. The performance of the membranes, which were denoted as GE0 (0% w/w of egg white), GE1 (1% w/w of egg white), GE2.5 (2.5% w/w of egg white) and GE5 (5% w/w of egg white), was evaluated for the removal of methylene blue from aqueous solution via membrane filtration system. The highest rejection of 96% and the best permeation of 15 L/m2.h were obtained for GE5 membrane. This finding is supported by bigger pore size (19.6 nm) with better uniformity as revealed by BET and FESEM analysis.